Allergen immunotherapy: what is the added value of real-world evidence from retrospective claims database studies?. (3rd May 2020) - Devillier, Philippe; Demoly, Pascal; Molimard, Mathieu
ABSTRACT: Introduction : Randomized controlled trials (RCTs) show that allergen immunotherapy (AIT) has proven long-term efficacy in patients with allergic rhinitis (AR). However, RCTs have limited generalizability and there is growing recognition that real-world evidence (RWE) is necessary to provide complementary data to those of RCTs, and corroborate their findings. Until recently, data from the real-world setting investigating the benefits of AIT for the treatment of patients with grass and birch pollen-associated AR were sparse, but new retrospective claims database studies from France and Germany have confirmed the sustained benefits of grass and birch pollen AIT in terms of significantly reduced progression of AR and asthma, and a significantly decreased risk of new-onset asthma. Areas covered : Here, we review the value of RWE used alongside data from traditional RCTs, and its potential strengths and limitations, and summarize the findings of the recent RWE studies investigating the benefits of AIT for the management of patients with grass and birch pollen-associated AR. Expert opinion : There is growing recognition of the necessity and value of RWE as a complement to data acquired in RCTs, to better understand the effects of AIT treatments in a broader, more representative patient population, and to help guide clinical decision-making.